Implementation of energy management system for a split-parallel hybrid electric vehicle with in-wheel motors - Zulkifli, S.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper discusses the development of an energy management and supervisory control system (EMS) for a hybrid electric vehicle (HEV). It is built on National Instruments' CompactRIO embedded controller and LabVIEW Real-Time software platform. The EMS functions as the primary vehicle controller whose objective is to achieve optimal operation of the hybrid propulsion system - reduced fuel consumption and self-sustaining energy storage, since the vehicle is a non-plug-in hybrid. The HEV derives its propulsion power from two sources - an internal combustion engine (ICE) and an electric motor. The EMS receives inputs of throttle position, vehicle speed, engine rpm and battery state of charge (SOC). Based on a certain control algorithm, it then determines the two sources' operation status and power distribution, and charging of battery pack. A graphical driver interface is implemented on a tablet PC with a TCP/IP connection to the EMS controller. A LabVIEW-based interface appears on a dynamically-controllable HTML page hosted by the web server function of the CompactRIO, enabling the driver to monitor and override control of the hybrid vehicle. Â© 2015 IEEE.